Pengaruh Penyuluhan Gizi menggunakan Media Audiovisual pada Pasien Hipertensi di Puskesmas Wonosari - Maulidia Safira, Nur Aida; Widajati, Endang; Soelistyorini, Dwie (NUTRITURE JOURNAL; Vol 3 No 3 (2024): Nutriture Journal, 2024)
Hypertension is often referred to as a silent killer because it does not show symptoms, which can lead to its presence going unnoticed. As a result, some people may still feel healthy and continue their usual activities. According to data from Riskesdas in 2018, the prevalence of hypertension in Indonesia was 34.1%. In East Java, the prevalence rate was reported to be 36.3%, and this prevalence increases with age. Given the relatively high prevalence rate, it is essential to educate the community about the causes of hypertension and the appropriate diet. Providing counseling through audiovisual media is one effective method to help control hypertension and inform the community on how to manage it. The type of research conducted is quasi-experimental, focusing on the impact of knowledge levels, food intake, and decreased blood pressure among subjects using a time series design. This research design involves only one group, so it does not require a control group (Sugiono, 2009). The treatment in this study was administered four times. Before the treatment, a pretest was given to the respondents, and after the treatment, they were given a posttest. The results indicate that the provision of nutritional counseling significantly improved knowledge levels (p = 0.000). For food intake, the following values were observed: energy intake (p = 0.047), protein intake (p = 0.009), fat intake (p = 0.032), carbohydrate intake (p = 0.030), potassium intake (p = 0.000), sodium intake (p = 0.000), systolic blood pressure (p = 0.000), and diastolic blood pressure (p = 0.000). The provision of nutritional counseling using audiovisual media has a positive effect on changes in knowledge levels, food intake, and blood pressure in hypertensive patients.